A Visual Framework For Dynamic Mixed Music Notation. Issue 1 (2nd January 2017) - Burloiu, Grigore; Cont, Arshia; Poncelet, Clement
Abstract: We present a visual notation framework for real-time, score-based computer music where human musicians play together with electronic processes, mediated by the Antescofo reactive software. This framework approaches the composition and performance of mixed music by displaying several perspectives on the score's contents. Our particular focus is on dynamic computer actions, whose parameters are calculated at runtime. For their visualisation, we introduce four models: an extended action view, a staff-based simulation trace, a tree-based hierarchical display of the score code and an out-of-time inspector panel. Each model is illustrated in code samples and case studies from actual scores. We argue the benefits of a multifaceted visual language for mixed music, and for the relevance of our proposed models towards reaching this goal.